Existence and multiplicity of radially symmetric solutions for nonlinear Schrödinger equations - Kinoshita, Tomoharu (Topological Methods in Nonlinear Analysis, 2023)
In this paper we study the following nonlinear Schrödinger equations in R^N: -Δ u + V(x)u= g(u),u H^1(R^N), where N 2, V C^1(R^N,R) and g C(R,R). For a wide class of nonlinearities, which satisfy the Berestycki-Lions type condition, we show the existence and multiplicity of radially symmetric solutions. We use a new deformation argument under a new version of the Palais-Smale condition.